Redistribution of Monocarboxylate 1 and 4 in Hippocampus and Spatial Memory Impairment Induced by Long-term Ketamine Administration - Ding, Runtao; Tan, Yaqing; Du, Ao; Wen, Gehua; Ren, Xinghua; Yao, Hui; Ren, Weishu; Liu, Huairu; Wang, Xiaolong; Yu, Hao; Yao, Jun; Li, Baoman; et al. (Frontiers in Behavioral Neuroscience, 2020)
The monocarboxylate transporters MCT1, MCT2, and MCT4 are essential components of the astrocyte-neuron lactate shuttle, which is a fundamental element of brain energetics. Decreased expression of monocarboxylate transporters can induce cognitive dysfunction of the brain. In present study, we established a mouse model of long-term ketamine administration by subjecting mice to a 6-month course of a daily intraperitoneal injection of ketamine. These mice demonstrated learning and memory deficits and a significant decline in MCT1 and MCT4 proteins in the hippocampal membrane fraction, while cytoplasmic MCT1 and MCT4 protein levels were significantly increased. In contrast, the levels of global MCT2 protein were significantly increased. Analysis of mRNA levels found no changes in MCT1/4 transcripts, although the expression of MCT2 mRNA was significantly increased. We suggest that redistribution of hippocampal MCT1 and MCT4, but not MCT2 up-regulation, may be related to learning and memory deficits induced by long-term ketamine administration.